(3TaGA GdYdjd aj HjGf GdTHg hGdeNjd heSGdc GdJYdjds - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3eMeO Hf YHO Gddg Hf SecGf GdSdeGSi s)
(3ChdgG (B:s
(3CeG HYO aEf EMJjGLc Edi TaGA GdZdjd ai HjGf eSGdc GdJYdjd hGSJNQJ Gddg ai ESYGac HeWdHc GdeSdc GdQGHY ai GdESJOdGd Ydi chf GdhUa YdI GdefGSHI s
(3BNQgG (B:s
(3gPG fgGjI eG CQOfG Cf fPcQg ai GdCQcGf GdNeSI ef GdbjGS ebJUQjf Ydi GdebUO GdPi CYQH Yfg dbH GdcJGH Je GdcJGH hddg GdMeO hGdefg s
(3bhHd hUMM SfI (B552(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1051s
Keywords: (3CUhd Gdabgs